EON UK CORPORATE RISK ASSESSMENT - Bedi, Rahul (2008)
In this world of greater uncertainty companies are continuously exposed to multiple risks which challenge their existence on a perpetual basis. These uncertainties have to be addressed and firms have to plan for risks faced by them.